2001
DOI: 10.1590/s1415-52732001000400005
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de energia e macronutrientes por adolescentes de escolas públicas e privadas

Abstract: RESUMO RESUMO O objetivo deste trabalho foi avaliar a adequação do consumo de energia e macronutrientes em adolescentes de escolas públicas (EPU) e privadas (EPR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
28

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 12 publications
0
4
0
28
Order By: Relevance
“…24 In a study that investigated Brazilian children and adolescents with JIA, Chaud et al 1 found excessive protein intake in 39% of the individuals assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In a study that investigated Brazilian children and adolescents with JIA, Chaud et al 1 found excessive protein intake in 39% of the individuals assessed.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][19][20][21][22][23] Regarding the low energy intake we found (41.7% in JIA patients and 45.5% in JSLE patients), our data are similar to those of studies involving healthy Brazilian subjects belonging to the same age group, with results ranging from 10.7 to 50%. 9,24,25 Some studies conducted with JIA patients have shown divergent results with regard to the energy intake, demonstrating low intake, 5,20 high intake, 21 or no difference between the values 2 when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O resultado obtido em relação ao consumo excessivo de proteína nos grupos AIJ e LES foi semelhante ao identificado em estudo com população brasileira saudável da mesma faixa etária 24 . Em crianças e adolescentes brasileiros com AIJ, Chaud et al 1 observaram consumo excessivo de proteína em 39% dos indivíduos avaliados.…”
Section: Aij (N = 48) Les (N = 22)unclassified
“…A ingestão elevada de lipídios -em torno de 30 a 40% -foi observada tanto na nossa população quanto em crianças e adolescentes brasileiros saudáveis 9,24 . Alterações do perfil lipídico são frequentes, especialmente em indivíduos com LES, e podem contribuir para o desenvolvimento futuro de complicações cardiovasculares 27 .…”
Section: Aij (N = 48) Les (N = 22)unclassified